The Influence of Competency and Employee Engagement on the Employee Development of PT Ardisi Herbalindo - Pramudiya, Bram; Supriadi, Yudi Nur (JURNAL MANAJEMEN MOTIVASI, 2025)
This study employs a quantitative approach to examine the influence of competence and employee engagement on employee development at PT Ardisi Herbalindo. Using a simple random sampling method based on Slovin's formula, 95 respondents were selected. Data were collected via questionnaires and analyzed using the Partial Least Squares (PLS) method. The findings indicate that: (1) competence has a positive and significant effect on employee development; and (2) employee engagement also exerts a positive and significant influence. These results offer both theoretical and practical contributions, expanding the human resource management literature and providing actionable insights for organizations, particularly PT Ardisi Herbalindo, in optimizing employee development through enhanced competence and engagement.